2021
DOI: 10.1186/s40359-021-00534-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of quality of life among medical students: results from a multicentric study

Abstract: Background Medical students have a worse perception of Quality of Life (QoL) and a high prevalence of psychosocial suffering when compared to the general population. The objective of this study was to investigate associated factors with Quality of Life of Brazilian medical students from an exploratory analysis in a cross-sectional study described in accordance with the STROBE (Strengthening the Reporting of Observational studies in Epidemiology) guidelines. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 80 publications
2
24
1
6
Order By: Relevance
“…The literature shows, furthermore, that nurses in the present study reported moderate levels of resilience. This finding is consistent with previous studies among other populations, e.g., Brazilian medical students [ 43 ] and the general Spanish university population [ 20 ]. As resilience is one of the key protective factors in mental health [ 15 ], nurses reporting low levels of resilience could benefit from receiving effective psychosocial interventions that lead to long lasting improvements in resilience [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…The literature shows, furthermore, that nurses in the present study reported moderate levels of resilience. This finding is consistent with previous studies among other populations, e.g., Brazilian medical students [ 43 ] and the general Spanish university population [ 20 ]. As resilience is one of the key protective factors in mental health [ 15 ], nurses reporting low levels of resilience could benefit from receiving effective psychosocial interventions that lead to long lasting improvements in resilience [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…O predomínio de estudantes do sexo feminino, na amostra, reflete uma tendência nacional e internacional na educação superior, principalmente em cursos da área da saúde (Martins, Silveira, & Silvestre, 2013;Miguel, Tempski, Kobayasi, Mayer, O uso de álcool em excesso, drogas ilícitas (atual ou passado) e tabagismo foi informado, por uma proporção considerável dos estudantes. A prevalência do uso de substâncias psicoativas (SPA) é elevada entre estudantes universitários brasileiros, uma vez que se encontram em um período de transição e adaptação a um novo contexto.…”
Section: Discussionunclassified
“…& Martins, 2021). Em alguns países, como Brasil, China e Reino Unido, as mulheres já representam a maior parte dos estudantes dos cursos de medicina(Jefferson, Bloor, & Maynard, 2015).…”
unclassified
“…Some recent studies carried out in different countries have reported modification in alimentary profiles associated with the lockdown. In particular, increased consumption of foods with high sugar content, such as chocolate and salty snacks, has been reported [32,33]. The possible explanation of these alimentary regimen changes can be explained to the increased levels of anxiety and the difficulties to find open grocery stores close to home [34].…”
Section: Discussionmentioning
confidence: 99%